Analysis of the Special Method of Tafsir As-Sa'di in Surah Al-Qamar - Haririe, Muhammad Ruhiyat; Rohmatulloh, Yasin; Zulaiha, Eni; Yunus, Badruzzaman M; Taufiq, Wildan (Jurnal Penelitian Ilmu Ushuluddin, 2025)
This study aims to analyze the methods and approaches of interpretation used by Abdurrahman bin Nashir As-Sa'di in the book Taysir al-Karim ar-Rahman fi Tafsir Kalami al-Mannan, especially in the interpretation of the letter Al-Qamar. This study is a qualitative study with a descriptive method, using primary data from the interpretation book and secondary data from related books and scientific articles. The results of the study indicate that As-Sa'di uses the bi al-ra'yi interpretation method with an ijmali approach. In most of his interpretations, he emphasizes the theological aspect (aqaidi), focusing on strengthening the creed and simple explanations that are easy for general readers to understand. Although he rarely cites narrations explicitly, As-Sa'di remains consistent with authentic sources in his interpretations. This study also identifies the advantages of As-Sa'di's interpretation method, namely explanations that are free from complexity and efforts to avoid disputes in the discourse of fiqh and kalam science, although As-Sa'di does not include many authoritative sources directly in his interpretations. This study recommends that a more in-depth study be conducted on the As-Sa'di interpretation method in a broader, deeper and more comprehensive manner to gain a complete understanding of the As-Sa'di interpretation.